Contemporary Islamic Law in Indonesia: The Fulfillment of Child Custody Rights in Divorce Cases Caused by Early Marriage - Idris, Ahmad Rusyaid; Khusaini, Muhammad; Al-Mansyuri, Syaiful Anwar (Faculty of Sharia, IAIN Metro, 2024)
This study aims to analyze the fulfillment of child custody rights in divorce cases due to early marriage using a contemporary Islamic law approach. A marriage license in Indonesia is only allowed to be granted to a man and woman from age 19 and above. The aim is to prevent early marriages which are very vulnerable to divorce due to the psychological immaturity of the couple. For example, Kotagajah Timur was observed to have a common case of divorce among underage people that married due to pregnancy outside of marriage. Therefore, this descriptive-analytical field study was conducted based on a phenomenological method. Moreover, data were collected using observation, interviews, and documentation. The results showed that divorcees from early marriages were unable to fulfill the provisions of Child Custody Rights. This was observed from the fact that the couple did not provide the required child protection after the divorce in addition to the non-fulfillment of other rights such as Nasab, Nafkah, Care (Hadhanah), and Child Education Patterns. Furthermore, the mother is required by the law to have full custody while the father provides living expenses. This requirement is observed to have been ignored because the mother is underage and lacks the maturity to perform the necessary obligations such as caring for and educating the children. Therefore, the children are discovered to be under the care of the parents of the mother.